Sporadic Medullary Thyroid Carcinoma: Towards a Precision Medicine - Matrone, Antonio; Gambale, Carla; Prete, Alessandro; Elisei, Rossella (Frontiers in Endocrinology, 2022)
Medullary thyroid carcinoma (MTC) is a neuroendocrine malignant tumor originating from parafollicular C-cells producing calcitonin. Most of cases (75%) are sporadic while the remaining (25%) are hereditary. In these latter cases medullary thyroid carcinoma can be associated (multiple endocrine neoplasia type IIA and IIB) or not (familial medullary thyroid carcinoma), with other endocrine diseases such as pheocromocytoma and/or hyperparathyroidism. RET gene point mutation is the main molecular alteration involved in MTC tumorigenesis, both in sporadic and in hereditary cases. Total thyroidectomy with prophylactic/therapeutic central compartment lymph nodes dissection is the initial treatment of choice. Further treatments are needed according to tumor burden and rate of progression. Surgical treatments and local therapies are advocated in the case of single or few local or distant metastasis and slow rate of progression. Conversely, systemic treatments should be initiated in cases with large metastatic and rapidly progressive disease. In this review, we discuss the details of systemic treatments in advanced and metastatic sporadic MTC, focusing on multikinase inhibitors, both those already used in clinical practice and under investigation, and on emerging treatments such as highly selective RET inhibitors and radionuclide therapy.